Urgency of Implementing Asymmetrical Local Elections in Indonesia under the 1945 - Fitriani Fitriani; Nawaz Syarif (Penerbit Goodwood, 2026)
Purpose: This study aims to analyse the urgency of implementing Asymmetric Regional Head Elections (Asymmetric Pilkada) in Indonesia as a solution to various problems plaguing the current direct e Local Strategylection system. Methodology/approach: This study uses a normative legal research method. This approach involves analysing primary legal materials, including the 1945 Constitution and related laws and regulations, as well as secondary legal materials such as academic literature and court decisions, particularly from the Constitutional Court. Results/findings: This study found that the symmetrical direct election system has caused significant problems, including very high costs that burden the regional budget, rampant money politics, intense social conflicts, and a high number of election disputes. The concept of ‘democratically elected’ in Article 18(4) of the 1945 Constitution is an open legal policy, which allows for both direct and indirect election models. Conclusions: The implementation of Asymmetric Regional Elections is urgent to overcome the shortcomings of the existing system. This model offers a flexible and contextual approach to regional elections, ensuring that the democratic process remains fair, honest, and honest without burdening regions that are not yet ready for direct elections. Limitations: This study is primarily conceptual and normative in nature. It relies on secondary data and legal analysis, thus lacking empirical validation through field research. The proposed implementation indicators require further operationalization and practical testing in various regional contexts. Contributions: This article contributes to the study of constitutional law and regional autonomy by offering a better legal framework for Asymmetric Regional Elections as a democratic yet context-sensitive election model, strengthening constitutional interpretation while promoting more efficient, accountable, and sustainable regional governance.